SMAD4 Somatic Mutations in Head and Neck Carcinoma Are Associated With Tumor Progression - Lin, Li-Han; Chang, Kuo-Wei; Cheng, Hui-Wen; Liu, Chung-Ji (Frontiers in Oncology, 2019)
Head and neck squamous cell carcinoma (HNSCC) incidence and mortality rate have been increasing worldwide. Therefore, understanding the genomic alterations involved in HNSCC carcinogenesis is a crucial issue for HNSCC diagnosis and therapy. The tumor suppressor gene SMAD4 (DPC4) at chromosome 18q21.1 belongs to the SMAD family, which mediates the TGF-β signaling pathway that suppresses epithelial cell growth. In this study, a multiplex polymerase chain reaction (PCR)-based next-generation sequencing (NGS) analysis was performed and 4.1% of tumors were found to harbor deleterious SMAD4 mutations. Experiments performed by knocking down the endogenous and exogenous SMAD4 expression revealed that SMAD4 suppressed the migration and invasion of HNSCC cells. Functional analysis results indicated that the missense mutation in SMAD4 MH1 domain may negatively affect the loss of suppression against tumor progression. Missense SMAD4 mutations are prognostic determinants in patients with HNSCCs, and this is the first study to use multiplex PCR-based NGS analysis to demonstrate the eminent occurrence of these missense SMAD4 mutations in HNSCC cells. The gene analysis performed here may facilitate the identification of SMAD4 mutation as a diagnosis marker or therapeutic target in head and neck cancer. Moreover, the analytic strategy proposed for SMAD4 mutation detection here may be validated as a platform to assist mutation screening.